Teachers’ perception in relation to the sensory processing of students with autism spectrum disorder - Monteiro, Rubiana Cunha [UNESP]; Dos Santos, Camila Boarini [UNESP]; Araújo, Rita de Cássia Tibério [UNESP]; Garros, Danielle Dos Santos Cutrim; Rocha, Aila Narene Dahwache Criado [UNESP] (FapUNIFESP (SciELO), 2020)
This study aimed to identify the perception of teachers in relation to the sensory processing of students with Autism Spectrum Disorder (ASD). Nineteen teachers of Early Childhood Education and early grades of Elementary Education from public schools in a municipality in the state of São Paulo, Brazil, participated in the research, as well as their 62 students. Data collection was carried out between the months of September 2018 and May 2019. A scale assessment of the Sensory Profile 2 of School Monitoring was used, which evaluates children and adolescents from the perspective of the teachers. The analysis of the results occurred through the categories of the instrument. In all categories, Quadrants (Sensory seeking, Sensory Avoiding, Sensory Sensitivity And Low Registration), Sensory and Behavioral Sections (Auditory, Visual, Tactile, Vestibular and Behavioral) and School Factors (School Factor 1, School Factor 2, School Factor 3 and School Factor 4 ), the classification of “More and Much More than the Majority of the Others” expressed the highest percentage, totaling, in all aspects assessed by the instrument 62.9%. The study identified that students with ASD, who have a characteristic profile of Sensory Integration dysfunctions are impacted by the condition of body structure and function in the teaching and learning processes and the participation in activities within the classroom. The results point to the importance of the occupational therapist’s actions in the school environment through collaborative work with the teacher, since the results in relation to the sensory profile directly interfere with the performance of students with ASD in view of the demands of activities in the school context.
Percepção de professores em relação ao processamento sensorial de estudantes com transtorno do espectro autista1
Keywords: Autism Spectrum Disorder; Occupational Therapy; School; Sensory Processing; Special Education